Analysis of the Correlation Between Tracer Utilization and Medical Record Document Loss at the Medical Record Unit of Harum Melati Clinic Pringsewu, 2025: Analisis Penggunaan Tracer Dengan Kehilangan Dokumen Rekam Medis Di Instalasi Rekam Medis Klinik Harum Melati Pringsewu Tahun 2025 - Irawan, Yhuni; Bahri, Yessiana Luthfia (Jurnal Rekam Medis dan Informasi Kesehatan, 2025)
The loss of medical record documents (misfiles) is a serious issue in health information management, as it can hinder medical services. One preventive measure that can be taken is the use of tracers as a tracking tool for medical record documents taken out of the storage area. The research objective was to analyze the use of tracers in relation to the loss of medical record documents at Harum Melati Clinic in Pringsewu 2025. This research uses a qualitative descriptive approach, with data collection techniques involving observation and interviews with two main informants and two triangulation informants. The study was conducted at Harum Melati Clinic from June 12nd to June 20th 2025. Data analysis was carried out through data collection, data reduction, and data presentation. The results showed that cases of lost medical record documents still occurred, mainly due to limited availability of tracers, inconsistent use of tracers by staff, and low adherence to Standard Operating Procedures (SOPs). The manual use of tracers still faces technical and disciplinary obstacles, which directly affect service efficiency. It is necessary to increase the number of tracers, strengthen SOP supervision, and provide regular staff training to prevent the loss of medical record documents and improve the quality of services at Harum Melati Clinic.